Tingkat minat penggunaan metode penelitian kuantitatif mahasiswa PGSD berdasarkan data skripsi Universitas Hamzanwadi - Tholibah, Ulfiana Baqiatul Husnul; Maritasari, Donna Boedi; Nurhidayati, Nurhidayati; Fatmawati, Siti (CT. Rajawali media Utama, 2025)
This study aims to describe the level of interest among students of the Elementary School Teacher Education Study Program at Hamzanwadi University in using quantitative research methods in writing their theses in 2024. The research method used is descriptive quantitative with a documentation study approach on 161 student theses. The analysis results show that 37% of the theses used quantitative methods, 35% used qualitative methods, and 28% used development methods (R&D). These findings indicate that although quantitative methods are still the primary choice, there is a trend of increasing use of other methods that adjust to the complexity and needs of the research topic. This study provides important insights for advisors and study programs in designing more relevant and contextual learning strategies for research methodology.